Association between eIF3α polymorphism and severe toxicity caused by platinum‐based chemotherapy in non‐small cell lung cancer patients. (10th January 2013) - Xu, Xiaojing; Han, Lifang; Duan, Li; Zhao, Yingchun; Yang, Huaping; Zhou, Boting; Ma, Rui; Yuan, Ruixia; Zhou, Honghao; Liu, Zhaoqian
<x xml:space="preserve">Abstract</x> Aim Platinum‐induced toxicity severely impedes successful chemotherapy in lung cancer patients. The nucleotide excision repair (NER) pathway is considered as one of the major factors contributing to platinum effects. Furthermore, genetic variances of the NER pathway influence platinum toxicity. eIF3α, over expressed in many malignancies, is an up‐stream gene of NER and could regulate its activity. The purpose of this study was to investigate whether eIF3α polymorphism is associated with severe platinum toxicity in patients with non‐small cell lung cancer (NSCLC). Methods Two hundred and eighty‐two incident NSCLC patients, from three different institutions, were enrolled and followed up. These patients were diagnosed and histologically confirmed with non‐small cell lung cancer. All patients accepted platinum based chemotherapy for at least two cycles. Twenty‐two SNPs of eIF3α were detected in these patients. Results eIF3α Arg803Lys C > T polymorphism was associated with cisplatin‐induced toxicity in NSCLC patients (P = 0.02, OR = 0.54, 95% CI 0.32, 93). T‐carrier subjects presented better tolerance to platinum nephrotoxicity, but poorer tolerance to ototoxicity. Conclusion eIF3α Arg803Lys was associated with platinum toxicity in NSCLC patients and could be considered as a predictor for pretreatment evaluation in lung cancer patients.